No sign of quitting: incidental exposure to "no smoking" signs ironically boosts cigarette‐approach tendencies in smokers. Issue 10 (30th September 2013) - Earp, Brian D.; Dill, Brendan; Harris, Jennifer L.; Ackerman, Joshua M.; Bargh, John A.
Abstract The unconscious mind tends to disregard negations in its processing of semantic meaning. Therefore, messages containing negated concepts can ironically prime mental representations and evaluations that are opposite to those intended. We hypothesized that the subtle presentation of a negated concept (e.g., "no smoking") would activate ironic motivational orientations as well. We tested this hypothesis in a public health context. Smokers viewed photographs in which "no smoking" signs were either inconspicuously embedded (prime condition) or edited out (control condition). Primed smokers showed amplified automatic approach tendencies toward smoking‐related stimuli, but not toward smoking‐unrelated stimuli: an ironic motivational response to exposure to the signs. Since passive priming effects generally serve to facilitate forms of action, not inhibit them, antismoking and other public health campaigns may ironically increase the very behaviors they seek to reduce.